Vitamin D Status in Patients with Type 2 Diabetes Mellitus in Makkah Region of Saudi Arabia - Dabbour, I.R.; Jazar, A.S.; Azzeh, F.S. (Pakistan Journal of Nutrition, 2016)
Deficiency of vitamin D is still a worldwide health problem. Although the sun is replete all over the year in Saudi Arabia, it has been shown that deficiency of vitamin D is an important health problem. The aim of this study was to investigate the association of serum 25-hydroxy vitamin D [25(OH)-D] in type 2 diabetic patients (T2DM) compared to control healthy subjects. A randomized case-control study was conducted and a total of 200 subjects were equally categorized in each group. A detailed basic information questionnaire was used. Serum levels of 25(OH)-D and others related biochemical analysis were also measured. According to our results, there were no significant differences (p>0.05) in age, serum 25(OH)-D level, parathyroid hormone (PTH), alkaline phosphatase (ALP) and BMI between case and control groups. On the other hand, there was a significant inverse relationship between age and serum 25(OH)-D level (r = -0.37, p<0.05), while a significant positive correlation between serum 25(OH)-D and intakes of vitamin D (r = 0.33, p<0.05) was observed. The mean value of serum 25(OH)-D was significantly higher (p<0.05) for the subjects who regularly played outdoor physical activities than those subjects who did not play regularly. Respect of income, the mean value of serum 25(OH)-D for subjects with low income was significantly (p<0.05) higher than those subjects with high income. Additionally, the mean value of serum 25(OH)-D for subjects who can write and read was significantly (p<0.05) higher than those illiterate subjects and subjects hold a university degree. The mean value of serum 25(OH)-D level for small family size was significantly (p<0.05) higher than those with large family size. The subjects in our study were generally deficient in 25(OH)-D irrespective of having T2DM, indicating a greater need for vitamin D supplementation.